Three Chinese children with Niemann-Pick disease type C with neonatal cholestasis as initial presentation - Yang, Rui (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2015)
OBJECTIVE: To analyze the clinical characteristics of three Chinese cases of Niemann-Pick disease type C patients with neonatal cholestasis as initial presentation, and enhance awareness of Niemann-Pick disease type C among pediatricians